Prevalence of Hepatitis B Virus Infection and Associated Factors Among High School Students in Shinshicho Town, Southern Ethiopia - Desta Tadewos; Sebsibe Tadesse; Tekle Ejajo; Tegegn Tadesse (SAGE Publishing, 2024)
Background: Early identification of people living with hepatitis B virus infection is required to initiate treatment and care, prevent community transmission, and expand vaccination. However, only an estimated 10% of people living with chronic hepatitis B infection are diagnosed, and only 2% are on treatment globally. This study aimed to assess the prevalence of hepatitis B virus infection and its associated factors among high school students in Shinshicho Town, southern Ethiopia. Methods: An institutional-based cross-sectional study was conducted among 380 high school students in Shinshicho Town, southern Ethiopia, from September to October 2022. A laboratory investigation of hepatitis B surface antigen was done to determine infection status. An odds ratio with a 95% confidence interval was used to declare statistical significance. Results: The prevalence of hepatitis B virus infection among high school students in Shinshicho town was observed to be 7.6% (95% CI: 5.5, 10.5%). Age 20 to 24 years [AOR: 2.7; 95% CI: (1.0-7.0)], rural residence [AOR: 3.4; 95% CI: (1.3-8.9)], and history of unprotected drug injection [AOR: 11.3; 95% CI: (3.7-34.8)] were independently associated with hepatitis B virus infection. Conclusion: A high prevalence of hepatitis B virus infection was observed among high school students in this study. Therefore, strengthening the school-based screen-and-treat program, especially targeting students from rural areas and young adults, and conducting awareness campaigns about the importance of practicing safe behaviors, such as avoiding unprotected drug injections, could contribute to the prevention and control of hepatitis B virus infection among high school students.